The Effect of the Use of Domino Arabic Media on the Mastery of Arabic Vocabulary of Grade VII Students MTs Negeri 1 Gorontalo City - Nor Sa’idah, Titik; Damhuri; I. Miolo, Mukhtar (Assuthur: Jurnal Pendidikan Bahasa Arab, 2025)
This study explores the effect of using Domino Arabic media on the mastery of Arabic vocabulary among seventh-grade students at MTs Negeri 1 Kota Gorontalo. The background of this research stems from the low vocabulary mastery among students, which is presumed to be caused by monotonous and less engaging teaching media. The main objective of this study is to determine the extent to which Domino Arabic media can influence students’ Arabic vocabulary acquisition. This research employed an experimental method with a pretest and post-test design applied to different student groups. The sample consisted of 27 students from grade VII, and data were collected through vocabulary tests conducted before and after using Domino Arabic. The results were analyzed using descriptive statistics and paired sample t-tests to assess the significance of the differences observed. The findings showed a significant improvement in students’ Arabic vocabulary mastery after using Domino Arabic. The average posttest score increased markedly compared to the pretest score. Pretest scores ranged from 5 to 54, with a mean of 12.96 and a standard deviation of 9.8. Meanwhile, post-test scores ranged from 36 to 95, with a mean of 77.11 and a standard deviation of 12.084. These results confirm that Domino Arabic effectively enhances students’ interest, engagement, and learning outcomes. It contributes to the field by providing empirical evidence of the benefits of game-based learning media in improving Arabic vocabulary mastery. This media can be considered a practical and innovative solution for Arabic language instruction in similar educational contexts.